2017
DOI: 10.1093/cid/cix975
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Predictors of Syphilis Prevalence in the General Population: Global Pooled Analyses of 1103 Prevalence Measures Including 136 Million Syphilis Tests

Abstract: Syphilis prevalence has been declining in every region by several percentage points per year. Nevertheless, the prevalence by region continued to vary, from as little as 0.1% in the European Region to as high as 3% in the African Region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 25 publications
(30 reference statements)
8
52
1
1
Order By: Relevance
“…The summarised and studyspecific risk of bias and precision assessments are shown in the appendix (pp [15][16][17][18][19][20][21][22][23][24][25][26][27] Table 3 shows the metaanalyses' results for the pooled average C trachomatis prevalence for each atrisk popula tion, stratified by type of assay used for infection ascertain ment. Current infection prevalence was estimated at 3•0% (table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The summarised and studyspecific risk of bias and precision assessments are shown in the appendix (pp [15][16][17][18][19][20][21][22][23][24][25][26][27] Table 3 shows the metaanalyses' results for the pooled average C trachomatis prevalence for each atrisk popula tion, stratified by type of assay used for infection ascertain ment. Current infection prevalence was estimated at 3•0% (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Studies applying nucleic acid amplification test (NAAT) and culture to the same biological specimen were included separately given our interest in studying their contribution to hetero geneity in C trachomatis prevalence, and in generating STIestimation correction factors based on assay type. [23][24][25] Studies applying other antigen detection assays to the same biological specimen were included only once based on assay sensitivity (direct fluorescence and enzyme linked immunoassays on genital samples were prioritised over Giemsa staining).…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…After the discovering of penicillin, the disease had almost-but only almost-disappeared from all corners of the world. According to the findings from a remarkable epidemiological study, involving 154 countries, using meta-analyses and meta-regressions, conducted from 1990-2016, showed that the median prevalence for syphilis worldwide was 1.4% [3]. This study also points to a decline of the prevalence rate of syphilis in the general population.…”
mentioning
confidence: 73%
“…2-5 The World Health Organization (WHO) Global Health Sector Strategy aims to reduce syphilis and gonorrhoea incidence over 2018-2030 by 90%, and to reduce the incidence of congenital syphilis to <50 cases per 100 000 live births by 2030. 6 China had 448 620 officially reported syphilis cases in 2012, almost doubling the number of cases reported in 2007; additionally, the rate of primary and secondary syphilis in 2012 was 13.44 cases per 100 000 population, increasing by 1.5 times since 2007. 7 China's syphilitic epidemic resurged with the commencement of economic prosperity in the 1980s, [8][9][10] especially in the areas of prosperous south-eastern seaboard.…”
Section: Introductionmentioning
confidence: 98%